Urgensi Peran Majelis Adat Aceh dalam Pengawasan Hukum Adat Istiadat di Aceh Barat: Studi Implementasi Qanun Nomor 5 tahun 2021 tentang Majelis Adat Aceh Kabupaten Aceh Barat - Handoyo, Budi; Fisa, Triansyah (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
Article 18B number [2] of the 1945 Constitution states that the State recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with community development and the principles of the Unitary State of the Republic of Indonesia, which are regulated by law. Article 18B, the Constitution provides the basis for the establishment of customary institutions as part of the policy for implementing regional autonomy in Aceh. Included in the Aceh autonomy policy is the establishment of customary institutions, including the Acehnese traditional assembly. the existence of the Aceh Customary Council, has been regulated in Chapter XIII of the Customary Institution Article 98 of Law Number 11 of 2006 concerning the Government of Aceh. In the process of monitoring the performance of the Aceh Customary Council, the Aceh Barat Regency has its own role in carrying out their duties and authorities as stipulated in Article 49 of the West Aceh Regency Qanun Number 5 of 2021 concerning the Aceh Customary Council, that the Aceh Regency Customary Council fosters and supervises the implementation of adat. based on Islam in the life of the people of West Aceh.